舌骨に連続する巨大な過長茎状突起を認めた1例 - 清水, 弦; 千足, 浩久; 藤田, 祐生; 今井, 智章; 加藤, 逸郎; 由良, 義明 (日本口腔外科学会雑誌, 2013)
A 60 -year- old man visited our hospital because of pain and discomfort around the left temporomandibular joint on maximum mouth-opening. The patient had been treated with nonsteroidal antiinflammatory drugs and corticosteroids by an otolaryngologist for a diagnosis of otitis externa, but the pain did not improve. There were no symptoms on turning his head and neck. Panoramic radiography and 3-dimensional computed tomography revealed a hypertrophied styloid process and ossified styloid ligament extending to the hyoid bone on the left side. The length of the styloid process and styloid ligament complex was 83 mm. Styloid process syndrome was diagnosed. With the patient under general anesthesia, reduction surgery of the styloid process was performed by a transcervical approach. Histopathological examination of the surgical specimen revealed bone tissue with thick trabecular bone and bone marrow. Cartilage tissue connected to the trabecular bone was also observed in the specimen. The patient's symptoms resolved after operation. Thirteen months after surgery, the patient remains free of symptoms.